Roma Employment in Hungary After the Post-Communist Transition - Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, 2010)
We analyze the magnitude and the causes of the low formal employment rate of the Roma in Hungary between 1993 and 2007. The employment rate of the Roma dropped dramatically around 1990. The ethnic employment gap has been 40 percentage points for both men and women and has stayed remarkably stable. Differences in education are the most important factor behind the gap, the number of children is important for female employment, and geographic differences play little role once education is controlled for. Conditional on employment, the gap in earnings is 0.3, and half of it is explained by educational differences.
Keywords: J15; J21; J70; 330; Roma minority; employment; education; Hungary; Ethnische Gruppe; Roma-Bevölkerung; Erwerbstätigkeit; Bildungsniveau; Systemtransformation; Ungarn